Radisotopic characterization as an analytical tool: current status, limitations and future challenges. (March 2015) - Deakin, Tom
In this review, we describe the growth of current state-of-the-art applications that rely on the 'online' analysis of radiolabeled samples, focus on the nature of the most common measurement techniques and provide some insight into the potential future developments of this powerful analytical tool. In particular, this review will concentrate on two common online analysis methods that utilize radioisotope detection and analysis systems coupled to chromatographic separations: radio-GC and radio-HPLC. The different sample conditions call for different approaches to the method of radiodetection in order to optimize the sensitivity and chromatographic resolution in each case. These methods are also compared with alternative analytical techniques, including accelerator MS and 'offline' counting.